WATER QUALITY OF RIVER GANGA ALONG THE WEST BENGAL STRETCH - MANDAL, S. K.; KOLE, S.; SENGUPTA, D.; SEN, S.; KOLE, R. K. (Journal of the Inland Fisheries Society of India, 2021)
Water quality of the river Ganga in West Bengal was assessed at 4 locations viz. Berhampore, Palta, Dakshineswar and Uluberia. Most of the physico-chemical parameters including metals were within BIS permissible limits for drinking. But the residues of some pesticides exceeded the EU permissible level for drinking. Significant spatial and temporal variation in the water quality was noted indicating higher pollution load during the monsoon and also along the downstream of the river. The low ionic concentration in water was well within the standard values with their dominance in the order: Ca2+ > Mg2+ > Na+ and SO4 2-> Cl- > NO3 - > F- . The river water appeared to be of medium salinity class for irrigation and was suitable for fisheries and aquaculture. However, pesticide residues like DDT may require special attention. Key words: Ganga, physico-chemical properties, metal, pesticide, permissible limit.